Cutaneous Immune-Related Adverse Events (irAEs) to Immune Checkpoint Inhibitors: A Dermatology Perspective on Management. Issue 1 (January 2021) - Muntyanu, Anastasiya; Netchiporouk, Elena; Gerstein, William; Gniadecki, Robert; Litvinov, Ivan V.
Immune checkpoint inhibitors have proven to be efficacious for a broad spectrum of solid organ malignancies. These monoclonal antibodies lead to cytotoxic T-cell activation and subsequent elimination of cancer cells. However, they can also lead to immune intolerance and immune-related adverse event (irAEs) that are new and specific to these therapies. Cutaneous irAEs are the most common, arising in up to 34% of patients on PD-1 inhibitors and 43% to 45% on CTLA-4 inhibitors. The most common skin manifestations include maculopapular eruption, pruritus, and vitiligo-like lesions. A grading system has been proposed, which guides management of cutaneous manifestations based on the percent body surface area (BSA) involved. Cutaneous irAEs may prompt clinicians to reduce drug doses, add systemic steroids to the regiment, and/or discontinue lifesaving immunotherapy. Thus, the goal is for early identification and concurrent management to minimize treatment interruptions. We emphasize here that the severity of the reaction should not be graded based on BSA involvement alone, but rather on the nature of the primary cutaneous pathology. For instance, maculopapular eruptions rarely affect <30% BSA and can often be managed conservatively with skin-directed therapies, while Stevens-Johnson syndrome (SJS) affecting even 5% BSA should be managed aggressively and the immunotherapy should be discontinued at once. There is limited literature available on the management of the cutaneous irAEs and most studies present anecdotal evidence. We review the management strategies and provide recommendations for psoriatic, immunobullous, maculopapular, lichenoid, acantholytic eruptions, vitiligo, alopecias, vasculitides, SJS/toxic epidermal necrolysis, and other related skin toxicities.